High Cod and Turbidity Removal in The Treatment of Polluted Pond Water Using Low Dosage of Pineapple Leaf Coagulant: A Preliminary Study - Husen, Rafidah; Idris, Juferi; Wakimin, Nur Diana; Mijim, Jimmy; Luncha, Lovelyna Eva Sunta ak Michael; Diman, Jacqueline Lindun; Lawrence, Michelle; Seli, Hazman; Jobli, Sunita; Mian, Vivien Jong Yi (Journal of Asian Scientific Research, 2021)
Coagulation process using low dosage of plant-based coagulant to remove high chemical oxygen demand (COD) and turbidity is important for water treatment. This study presents the treatment of pond water using plant-based pineapple leaf coagulant to achieve high COD and turbidity removal. The coagulation was performed using a jar test experiment of pond water at different pH followed by different dosages of pineapple leaf coagulant. It was found that the highest COD and turbidity removal ranged between 94.1 – 94.6 % and 88.3 – 88.4 % at pH 8 respectively, using low dosage (50 mg L-1) of pineapple leaf coagulant. The final COD and turbidity values ranged between 7.3 – 8.0 mg L-1 and 17.7 – 17.8 formazin turbidity unit (FTU) respectively, which are lower compared with results from other studies that used high dosage coagulants. Moreover, the final pH, COD, turbidity, dissolved oxygen (DO), and total suspended solid (TSS) values of the treated pond water were below the standard limits set by the National Water Quality Standards for Malaysia (NWQSM) class IIB, which represents water bodies suitable for recreational use with body contact (DOE, 2016). Therefore, it is expected that the newly-formulated waste utilisation of pineapple leaf coagulant can reduce the usage of chemical coagulants and can further be used for different types of water.